METHODS OF EEG ARTIFACTS ELIMINATION - Plechawska-Wójcik , Małgorzata (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
Registration of electroencephalography signals (EEG) is almost always associated with recording different kinds of artifacts that makes it difficult to read and analyze collected data. These artifacts may be noticeable in the individual channels, but very often they have to be adjusted over several channels simultaneously. Their origin can be varied. Among the most typical are network and hardware artifacts as well as several types of muscle artifacts, derived from the tested person. In recent years increased interest in EEG studies might be noticed. EEG signals are applied not only in the outpatient and clinical applications, but also in psychological analyses and in construction of modern human-machine interfaces. This article presents a case study of classification analysis application in EEG artifact correction tasks.